Work Accident at Sugar Farmers in Banyumas Regency (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
A work accident is an accidental event in the employment relationship, including diseases of the working relationship, the accident that happened on the way go to work, and coming home in the usual way. Work accidents can be experienced by sugar farmers. In Banyumas Regency, there are about 26.580 Sugar farmers. Based on Kesra Setda Banyumas Regency, from 2017 to November 2019 there were 323 cases of sugar farmers accidents, with 236 disabilities and 87 deaths. The purpose is to analyze the risk factors of work accidents consisting of behavioral and environmental factors. The method is an analytical survey with a cross-sectional approach. The sample was 200 people in Cilongok Districts. Data analysis includes univariate, bivariate, and multivariate. The results show that behavioral factors significantly associated with work accidents are breakfast status (p = 0,010) and unhealthy conditions (p = 0,002). Environmental factors significant to work accidents are past medical history (p = 0.000) and protein adequacy (p = 0,000). Recommendations for this research are socialization about the importance of breakfast and paying attention to the body condition before climbing, also training energy consumption diet of protein corresponding to the workload.